Integrasi Nilai-Nilai Islam dalam Pengelolaan Mutu Pendidikan di SMP Negeri 8 Pamekasan - Wahyuni, Amalia Desy; Solichin, Mohammad Muchlis (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
The quality of education involves two very important aspects, namely the process and results. The view of education as a mandate must be owned by every quality manager, so as not to lose the vision and spirit of transcendent talit as, namely the view and belief that in managing the quality of education is a task that must be maintained and carried out as a form of devotion to God. SMP Negeri 8 Pamekasan is one of the junior secondary education institutions that incorporates Islamic values in its education quality management. This study applied descriptive qualitative method with data collection through interviews, observation and documentation. The results show that quality management by integrating Islamic values includes quality planning with the school's vision-mission and curriculum that integrates Islamic values, moral formation and the establishment of short-term and long-term goals. Furthermore, quality supervision and evaluation are carried out with a fair and transparent assessment system and the enactment of a feedback mechanism for improvement. Therefore, to realize quality management based on Islamic values, the development of educators professionalism needs to be carried out with training and competency development as well as a culture of continuous learning among educators.